A meta-analysis uncovers the first sequence variant conferring risk of Bell’s palsy - Astros Th. Skuladottir (Nature Portfolio, 2021)
Abstract Bell’s palsy is the most common cause of unilateral facial paralysis and is defined as an idiopathic and acute inability to control movements of the facial muscles on the affected side. While the pathogenesis remains unknown, previous studies have implicated post-viral inflammation and resulting compression of the facial nerve. Reported heritability estimates of 4–14% suggest a genetic component in the etiology and an autosomal dominant inheritance has been proposed. Here, we report findings from a meta-analysis of genome-wide association studies uncovering the first unequivocal association with Bell’s palsy (rs9357446-A; P = 6.79 × 10−23, OR = 1.23; N cases = 4714, N controls = 1,011,520). The variant also confers risk of intervertebral disc disorders (P = 2.99 × 10−11, OR = 1.04) suggesting a common pathogenesis in part or a true pleiotropy.